SANGGAR SATAMPANG BANIAH DALAM INDUSTRI SENI PERTUNJUKAN DI SUMATERA BARAT: TINJAUAN MANAJEMEN SENI PERTUNJUKAN - Afiatri Gelurena; Indrayuda Indrayuda; Herlinda Mansyur (FBS Universitas Negeri Padang, 2014)
Abstract The purpose of this article is to discuss the management of art exhibition of Sanggar Satampang Baniah in Padan. This was a qualitive study which employed descriptive method. The instrument of this study was the researcher herself, who conducted field observation which was supported by camera, writing materials, and tape recorder. The data were analyzed based on the following steps: collexting the data, reduction, presenting, and making conclusion. The result of the study revealed that sanggar Satampang Baniahh used open management, production management, and marketing management in its activities. These three types of management are based on the context of the managemenet of art exhibition. Keywords: management, performing arts, studio.